Analysis of investment strategy in Indonesian consumer goods industry: Benjamin Graham's approach - Aditya Achmad Rakim; Mohammad Iqbal; Isra Misra (Diponegoro International Journal of Business, 2022)
Shares price fluctuations cause investors to take irrational actions. An assessment of investment valuation is needed to deal with market fluctuations so as to reduce investment risk. Benjamin Graham Formula is an investment strategy by comparing the fair value of the shares with the shares price to help investors in making investment decisions. Benjamin Graham's value investing strategy is a strategy of valuing shares whose actual value is higher than market value, thereby finding significant returns over the long term. This research is quantitative descriptive. Based on the selection criteria for the Benjamin Graham method, the researcher suggests buying ADES shares. The firms share price is currently undervalued. CEKA shares have an undervalued value, this can be used as an alternative consideration in making investment decisions.